(untitled) (Research, Society and Development, 2020)
This study aimed to investigate the perceptions and meanings attributed by teachers of a public school in the central region of the state of Rio Grande do Sul (RS) regarding the interdisciplinary theme and the repercussions on their teaching practice. Data were collected from an open questionnaire, analyzed qualitatively, using the Content Analysis technique proposed by Bardin. From the analysis of the teachers’ responses to the questionnaire, two major thematic categories emerged: Characterization of Interdisciplinarity and Interdisciplinary Practices. It was concluded that teachers conceive interdisciplinarity as (i) integration of subjects and contents, (ii) teaching and learning methodology and, (iii) integration of areas based on themes. Regarding interdisciplinary practices, teachers recognize the importance of collaborative work, dialogue between teachers and mastery of the content of their discipline to develop interdisciplinary actions. On the other hand, they point out the lack of time for planning and work overload as the main factors that hinder the insertion of interdisciplinary practices in their school context.